Filsafat Ilmu sebagai Landasan Pengembangan Ilmu Pendidikan - Mardinal Tarigan; Feby Annisa Yasmin; Akrizal Rifai; Yusriani Yusriani; Khairul Azmi (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The philosophy of science clarify the existence of science to the other science that requires knowledge as a medium of thinking and means of scientific communication. These are language, logic, mathematics, statistics, and other data analysis techniques. Specifications and independency science faced by the increasing number problems that can not be answered by science, therefore, philosophy appears as the answer. Philosophy gives an explanation or an answer onthat problems substantial and radical, while the science continues to develop it self- in its limit , while still radically criticized, process or the interaction basically is a field of philosophy of science. Philosophy of science therefore can be put as an attempt to bridge the gap between the philosophy and science, so that science does not despise the philosophy, and the philosophy does not see science as a superficial understanding of nature . Reality is “what is naturally “ or existence , while the appearance is that “artificially real“. Also how the relationship to both with subject /human. Epistemology is considered synonymous with the theory of knowledge. At the present time theory of knowledge can not be ignored. Epistemology of education science related to know how science education obtaining gain processing, what is the procedure to get the true scientific knowledge. Axiologiy related to what is the advantages of science education, what ethical relationship with science and its application science education in daily life . Key words : the philosophy of science, education, ontology, epistemology, axiology.